2002
DOI: 10.1182/blood-2002-05-1423
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for Wiskott-Aldrich syndrome: rescue of T-cell signaling and amelioration of colitis upon transplantation of retrovirally transduced hematopoietic stem cells in mice

Abstract: The Wiskott-Aldrich syndrome (WAS) is an X-linked primary immunodeficiency that is caused by mutations in the recently identified WASP gene. WASP plays an important role in T-cell receptormediated signaling to the actin cytoskeleton. In these studies we assessed the feasibility of using retroviral gene transfer into WASP-deficient hematopoietic stem cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 40 publications
(51 reference statements)
4
83
0
Order By: Relevance
“…The improvement in autoimmune colitis has also been obtained following transplantation of retrovirally transduced BM cells utilizing a strong viral LTR promoter to express the WAS transgene. 24 Altogether these results suggest that a strong promoter system does not appear to be essential to express the WAS transgene to obtain significant therapeutic benefit. Besides the improvement of the colitis, we also report that the WAS LV can increase the thymopoiesis in BM-reconstituted mice.…”
Section: Discussionmentioning
confidence: 98%
“…The improvement in autoimmune colitis has also been obtained following transplantation of retrovirally transduced BM cells utilizing a strong viral LTR promoter to express the WAS transgene. 24 Altogether these results suggest that a strong promoter system does not appear to be essential to express the WAS transgene to obtain significant therapeutic benefit. Besides the improvement of the colitis, we also report that the WAS LV can increase the thymopoiesis in BM-reconstituted mice.…”
Section: Discussionmentioning
confidence: 98%
“…Of 13 survivors of MUD transplants, 10 (76.9%) have excellent clinical outcome with no signs attributable to WAS, including three with previous autoimmune disease (no. 10,19,20). In contrast, both patients treated by MMRD BMT died early after transplant.…”
Section: Lymphoid Reconstitution and Functionmentioning
confidence: 96%
“…This may also impact on future therapeutic strategies for WAS such as gene therapy. A number of investigators have pursued gene replacement as an alternative strategy for WAS using mouse models [20][21][22][23][24] or by transducing human T cells. [25][26][27] However, given that the animal model fails to fully recapitulate the platelet defects seen in humans, 28 the direct relevance of these approaches to correction of human WAS…”
Section: Discussionmentioning
confidence: 99%
“…In particular, N-WASP, which shares 50% homology with WASP, may serve specific and redundant function with WASP in hematopoietic cells. In fact, we have shown that expression of N-WASP in WASP-deficient T cells partly restores CD3-mediated proliferation, implying that WASP and N-WASP might share functions in T cells (25).…”
mentioning
confidence: 98%